Efektivitas Dosis Pupuk Kotoran Ayam terhadap Pertumbuhan dan Produksi Rumput Setaria (Setaria splendida) pada Defoliasi Umur Berbeda - Ibrahim, Serli; Saputra, Agung (Fakultas Peternakan Universitas Madako Tolitoli, 2025)
This study aimed to evaluate the effectiveness of chicken manure fertilizer doses on the growth and yield of setaria grass (Setaria splendida) at different defoliation ages. The experiment was arranged in a Randomized Block Design (RBD) with four treatments of chicken manure doses, namely P0 (without fertilizer), P1 (3 kg/plot), P2 (6 kg/plot), and P3 (9 kg/plot), each with three replications. The observed parameters included plant height and fresh weight at defoliation ages of 60, 70, and 80 days, analyzed using analysis of variance (ANOVA) followed by the Honestly Significant Difference (HSD) test when significant differences were found. The results showed that chicken manure fertilizer had no significant effect (P>0.05) on plant height or fresh weight at all defoliation ages. However, the application of 6 kg/plot (P2) tended to produce better growth and yield, particularly at the first defoliation (60 days). At 70 and 80 days, the effect of fertilizer decreased as the plants entered the generative phase. These findings indicate that the response to organic fertilizer is more optimal during the early vegetative phase, while its influence declines with increasing plant age. Therefore, a moderate dose of chicken manure can be recommended to enhance the vegetative growth of setaria grass while maintaining efficient use of organic fertilizers.